Vibrio parahaemolyticus and Vibrio vulnificus in vitro biofilm dispersal from microplastics influenced by simulated human environment - Leighton, Ryan E.; Xiong, Liyan; Anderson, Gracie K.; Astarita, Grace M.; Cai, Guoshuai; Norman, Robert Sean; Decho, Alan W. (Frontiers in Microbiology, 2023)
Growing concerns exist regarding human ingestion of contaminated seafood that contains Vibrio biofilms on microplastics (MPs). One of the mechanisms enhancing biofilm related infections in humans is due to biofilm dispersion, a process that triggers release of bacteria from biofilms into the surrounding environment, such as the gastrointestinal tract of human hosts. Dispersal of cells from biofilms can occur in response to environmental conditions such as sudden changes in temperature, pH and nutrient conditions, as the bacteria leave the biofilm to find a more stable environment to colonize. This study evaluated how brief exposures to nutrient starvation, elevated temperature, different pH levels and simulated human media affect V. parahaemolyticus and V. vulnificus biofilm dispersal and processes on and from low-density polyethylene (LDPE), polypropylene (PP), and polystyrene (PS) MPs. Both species were able to adequately disperse from all types of plastics under most exposure conditions. V. parahaemolyticus was able to tolerate and survive the low pH that resembles the gastric environment compared to V. vulnificus. pH had a significantly (p ≤ 0.05) positive effect on overall V. parahaemolyticus biofilm biomass in microplates and cell colonization from PP and PS. pH also had a positive effect on V. vulnificus cell colonization from LDPE and PP. However, most biofilm biomass, biofilm cell and dispersal cell densities of both species greatly varied after exposure to elevated temperature, pH, and nutrient starvation. It was also found that certain exposures to simulated human media affected both V. parahaemolyticus and V. vulnificus biofilm biomass and biofilm cell densities on LDPE, PP and PS compared to exposure to traditional media of similar pH. Cyclic-di-GMP was higher in biofilm cells compared to dispersal cells, but exposure to more stressful conditions significantly increased signal concentrations in both biofilm and dispersal states. Taken together, this study suggests that human pathogenic strains of V. parahaemolyticus and V. vulnificus can rapidly disperse with high cell densities from different plastic types in vitro. However, the biofilm dispersal process is highly variable, species specific and dependent on plastic type, especially under different human body related environmental exposures.